2007
DOI: 10.1108/02686900710772573
|View full text |Cite
|
Sign up to set email alerts
|

Audit costs, material weaknesses under SOX Section 404

Abstract: Purpose -Section 404 of the Sarbanes-Oxley Act (SOX) of 2002 required companies to report on the effectiveness of their internal controls over financial reporting. Auditors also must attest to, and report on, the assessment of the effectiveness of internal control over financial reporting made by the management of the company being audited. The purpose of this paper is to provide analyses of audit fee costs and material weaknesses reported for companies of different sizes after the effective date of Section 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…In light of AS No. 5, such management requests are in line with standards and considered reasonable given the additional burden placed on the IAF through SOX 404 and the related significant increases in overall IAF costs (Foster et al, 2007;Kuhn and Sutton, 2010). Additionally, ancillary IT audit activities such as SOX compliance testing can be effectively executed remotely (i.e., via telework) and are among the easiest tasks for IAF to outsource (Pyzik, 2012).…”
Section: Background Theory and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…In light of AS No. 5, such management requests are in line with standards and considered reasonable given the additional burden placed on the IAF through SOX 404 and the related significant increases in overall IAF costs (Foster et al, 2007;Kuhn and Sutton, 2010). Additionally, ancillary IT audit activities such as SOX compliance testing can be effectively executed remotely (i.e., via telework) and are among the easiest tasks for IAF to outsource (Pyzik, 2012).…”
Section: Background Theory and Hypothesesmentioning
confidence: 96%
“…The Act both eliminated the option of outsourcing IT audits to incumbent auditors (SOX 201(a)) and substantially increased internal control system evaluation and documentation requirements (SOX 404) (Aguilar, 2005). The accompanying surge in compliance costs was frequently criticized in the business press as disproportionate (Blaskovich and Mintchik, 2007;Foster et al, 2007). Reacting to this criticism, the Public Company Accounting Oversight Board (PCAOB) adopted Auditing Standard No.…”
Section: Introductionmentioning
confidence: 98%
“…Prior studies have found that material weaknesses in internal control have been reported against SOD, period-end reporting, account-specific processes, and account reconciliation (Ge & McVay, 2005;Foster et al, 2007), potentially resulting in severe penalties. How managers use an ERP system to mitigate these weaknesses is therefore of interest to both researchers and practitioners.…”
Section: Concluding Commentsmentioning
confidence: 98%
“…Terminating the access of ex-employees is essential, as avoiding SOD disagreements is a major concern for SOX auditors, particularly in high-risk companies such as multinational organizations where there are large numbers of employees and systems access must be continually monitored and reviewed (Doyle et al, 2007). 4) Training: Lack of financial reporting expertise, including an absence of appropriate technical skills among staff, is a key reason for accounting errors and misstatements (Foster et al, 2007;Ge & McVay, 2005;Stoel & Muhanna, 2011). Unqualified staff can result in a failure to identify and solve accounting problems as well as a failure to perform effective reviews.…”
Section: Internal Controls Over Financial Reportingmentioning
confidence: 99%
See 1 more Smart Citation